Economic costs and health-related quality of life associated with individual specific reminiscence: Results from the InspireD Feasibility Study. (October 2020) - Ferry, Finola; Ryan, Assumpta; McCauley, Claire O; Laird, Elizabeth A; Gibson, Aideen; Mulvenna, Maurice D; Bond, Raymond; Bunting, Brendan; Curran, Kevin
Recent studies have focused on the use of technology to support reminiscence but there remains a dearth of research on the health costs and benefits associated with this intervention. The aim of this study was to estimate costs and quality of life associated with a home based, individual specific reminiscence intervention, facilitated by an iPad app for people living with dementia and their family carers, with a view to informing a future cost-effectiveness analysis. Use of community health and social care services, hospital services, prescribed medication and informal caregiving was assessed using an adapted version of the Client and Socio-Demographic Service Receipt Inventory (CSRI) at baseline and 3-month follow-up. Quality of life was assessed at baseline, 6-week and 3-month follow-up using the EQ5D, DEMQOL and DEMQOL proxy instruments. Results showed that average health and social care costs were £29, 728 per person at baseline (T0) and £33, 436 after 3 months (T2). Higher T2 costs were largely accounted for by higher informal caregiving costs. There was an overall increase in health-related quality of life over the duration of the intervention, although there were notable differences in index scores generated by the EQ5D (0.649, 0.652 and 0.719) and DEMQOL instruments (0.845, 0.968 and 0.901). The study concluded that a full cost-effectiveness analysis could incorporate a similar range of cost-categories with minor amendments to the CSRI to improve the accuracy of cost estimation. Furthermore, a larger sample size, randomisation and longer follow-up period are required to allow potential effects of the intervention to be realised and differences between intervention and control groups to be accurately detected.